Structural evolution on medium-range-order during the fragile-strong transition in Ge15Te85. (1st May 2017) - Wei, Shuai; Stolpe, Moritz; Gross, Oliver; Hembree, William; Hechler, Simon; Bednarcik, Jozef; Busch, Ralf; Lucas, Pierre
Abstract: Using synchrotron X-ray scattering, we investigate liquid Ge15 Te85 spanning a wide temperature range from near T g to the melt, and demonstrate that the density anomaly and fragile-strong transition are not only related to short-range-order (SRO) structural change (e.g. Peierls-like distortion), but also accompanied by a remarkable development of medium-range-order (MRO). The latter manifests as an emerging pre-peak in total structure factor S ( Q ) and atomic pair correlations on the length scale of ∼8 Å in the real space G ( r ) function. The results highlight the role of medium-range structural ordering in the evolution of the configurational entropy which, according to the Adam-Gibbs theory, can be linked to the fragile-strong transition (FS-transition). Based on the relation between structure and liquid dynamics, the FS-transitions at high pressures are examined in terms of experimental data and the Ehrenfest relation. This work identifies the length scale for the atomic correlations in MRO structural evolutions and presents a structural approach to exploring liquid dynamics, which may be useful for investigating relevant phase-change alloys. Graphical abstract: Image 1